MM-PNEMO: A Mathematical Model to Assess Handoff Delay and Packet Loss - Islam, Shayla; Hashim, Aisha Hassan Abdalla; Hasan, Mohammad Kamrul; Razzaque, Md. Abdur (Institute of Advanced Engineering and Science, 2019)
Wireless networks incorporate Mobile Nodes (MNs) that use wireless access networks to communicate. However, the communication among these MNs are not remained stable due to the poor network coverage during inter mobility. Moreover, the wireless nodes are typically small that results in resource-constrained. Thus, it is uphill to use algorithms having giant processing power or memory footprint. Accordingly, it is essential to check schemes consistently to evaluate the performance within the probable application scenario. To do so, numerical analysis could be a notable method to grasp the performance of mobility management schemes as well as the constraint of evolving mobility management solutions specifically for multi-interfaced MR in Proxy NEMO environment. This paper analyzes handoff performance by using a mathematical model of Multihoming-based scheme to support Mobility management in Proxy NEMO (MM-PNEMO) environment. Moreover, a comparative study has been made among the standard Network Mobility Basic Support Protocol (NEMO BSP), Proxy NEMO (PNEMO) and MM-PNEMO scheme respectively. The performance metrics estimated for these schemes are mainly handoff delay and packet loss. This paper also analysed the packet loss ratio and handoff gain as a function of cell radius, number of SMR and velocity respectively. It is apparent that, the MM-PNEMO scheme shows lower packet loss ratio (1%) compared to NEMO-BSP (11%) and P-NEMO (6%).